Hematological and Biochemical Alterations of Andaliman (Zanthoxylum Acanthopodium Dc) with Doxorubicin Induced in White Wistar Rat - Prayoga, Andre; Dalimunthe, Aminah; Zumaira; Salim, Emil (International Journal of Ecophysiology, 2025)
Doxorubicin, a well-known chemotherapy drug, is associated with cardiac toxicity primarily due to oxidative stress. This oxidative stress leads to the production of reactive oxygen species and a subsequent decline in antioxidant levels. As doxorubicin induces the formation of free radicals and decreases endogenous antioxidants, it triggers various hematological and biochemical abnormalities. Consequently, the use of antioxidants has been proposed as a strategy to mitigate this damage. This study focuses on the administration of ethanol extract from Andaliman (EAF) fruit, recognized for its rich array of metabolites and antioxidant properties, which may serve as a cardioprotective agent against the adverse effects of doxorubicin. The research involved comprehensive observations, including hematological and clinical chemistry examinations. The findings indicate that EAF demonstrates protective effects by enhancing hematological and clinical chemistry parameters in male Wistar rats subjected to doxorubicin. Notably, these improvements were statistically significant when compared to the control group. Given its promising results, further exploration of EAF as a protective agent for hematological and biochemical health warrants attention and development.